Isolated Ocular Tuberculosis Presenting as Unilateral Anterior Scleritis in an Immunocompetent Adolescent: A Case Report - Armel Mamihaja Andrianiaina; Rova Malala Fandresena Randrianarisoa; Placide Raharitina; Hervéat Ramanandafy; Hanta Marie Danielle Vololontiana; Marie Ida Rahatamalala (Journal of Case Reports and Reviews in Medicine, 2026)
Ocular tuberculosis is a rare form of extrapulmonary tuberculosis that can affect virtually any ocular tissue. We report the case of a 15-year-old adolescent from a tuberculosis-endemic region who presented with unilateral redness of the left eye and blurred vision, without pain, photophobia, or systemic symptoms, and with no relevant medical history. The condition failed to respond to topical corticosteroid and non-steroidal anti-inflammatory treatment, prompting further investigation. A comprehensive infectious and autoimmune work-up was negative, while a tuberculin skin test (7 mm induration) and a QuantiFERON-TB Gold assay were both positive, despite normal chest radiography, negative sputum smear microscopy, and a negative GeneXpert MTB/RIF assay. A diagnosis of tuberculous scleritis was made, and the patient was treated with a standard four-drug antituberculous regimen combined with oral corticosteroids. Ocular redness resolved completely and vision improved within three weeks, with no recurrence at follow-up. This case illustrates that ocular tuberculosis should be considered in the differential diagnosis of persistent, treatment-resistant ocular inflammation in tuberculosis-endemic areas, even in the absence of pulmonary or systemic disease.